2016
DOI: 10.5688/ajpe80342
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Certificate Program Participants’ Perceptions of Mentor-Mentee Relationships

Abstract: Objective. To assess teaching certificate program (TCP) participants' perceptions of mentor-mentee relationships. Methods. A 15-item survey instrument was administered to all 2014-2015 participants of the Indiana Pharmacy Teaching Certificate (IPTeC) program. Results. One hundred percent of IPTeC program participants (83/83) responded to the survey. The majority of participants indicated that having a professional mentor was either very important (52%) or important (47%) to their professional development and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…In studies on pharmacists receiving training, advantages in the provision of services, improved professional practice, and feeling more confident in patient care, were recognized [ 75 77 ]. Mentoring works as a dynamic and reciprocal relationship between a specialist with experience and expertise (mentor) and a beginner (the mentee), in order to guide and share experiences, is important to enhance the mentee’s professional development [ 78 , 79 ]. In the health field, mentoring tools help practitioners improve patient outcomes as well as develop specific skills and behaviors [ 80 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…In studies on pharmacists receiving training, advantages in the provision of services, improved professional practice, and feeling more confident in patient care, were recognized [ 75 77 ]. Mentoring works as a dynamic and reciprocal relationship between a specialist with experience and expertise (mentor) and a beginner (the mentee), in order to guide and share experiences, is important to enhance the mentee’s professional development [ 78 , 79 ]. In the health field, mentoring tools help practitioners improve patient outcomes as well as develop specific skills and behaviors [ 80 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Teaching and learning curricula provide foundational teaching and scholarship exposure to pharmacy residents and fellows. [1][2][3][4][6][7][8][9][10][11][12][13][14][15][16][17]19 While it is important to evaluate the quality and impact of these programs, it is also necessary to seek input from employers about the value of these programs in recruiting qualified pharmacy faculty. Successful recruitment of qualified faculty is not only important to individual institutions, but the academy as a whole.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] American Society of Health-System Pharmacists (ASHP) accreditation standards for postgraduate year one (PGY1) pharmacy residency programs include specific competencies for teaching and learning, and TLC programs are often incorporated as requirements for pharmacy residency completion in order to facilitate resident mastery of teaching-related competencies. 5 As such, the availability of TLC programs has grown significantly over the last 15 years, [6][7][8][9][10][11][12][13][14][15][16][17] with approximately 70 programs affiliated with colleges and/or schools of pharmacy currently available throughout the United States (US). 3,4 As the recruitment of qualified faculty is vital to the ongoing success of pharmacy education, TLC programs can play a vital role in helping to prepare faculty to meet these expectations.…”
Section: Introductionmentioning
confidence: 99%
“…In the end, strengthening the student teaching mentors and student teaching interns' relationship reduces preparation gap (Gordon et al in Walsh, 2018). As Sheehan et al (2016) concluded in their study that the participants place high importance on the adequate guidance of a mentor. For the longest period, student teaching internship is a school-based activity with actual face-to-face engagement.…”
Section: Introductionmentioning
confidence: 96%